Budaya Organisasi dalam Menciptakan Daya Saing Menuju Sustainabilitas Perguruan Tinggi - Sukatin, Sukatin; Fajri, Muhammad Rizkal (Institut Agama Islam Negeri Lhokseumawe, 2021)
Organizational culture is believed to be an enabler in increasing competitive advantage in higher education. This article evaluates the introduction of higher education into the development agenda and the introduction of sustainable development goals (SDGs) as a parallel but fragmented multilateral agenda and university reorientation. The research method uses qualitative methods with data from interviews, observations and documentation. The results of the study show the manifestation of organizational culture in creating a competitive advantage for universities. The research findings highlight the framework of the organizational culture building model and its framework (competing value framework). In addition, the results of the study indicate the need for strategic planning; adaptation of technological renewal through the practice of a culture of innovation; development of a partnership-based higher education network; interpersonal modalities of higher education service quality; performance improvement through service systems and effective leadership. The focus of attention leads to a competitive advantage strategy model based on university sustainability development. The important role of multi-stakeholder networks is to become a liaison facilitator who mediates between organizational culture and university competitive advantage. The originality of the value of this research contributes to filling the gaps in the literature on cultural studies and organizational behavior in the higher education sector, where studies on organizational culture in relation to creating competitive universities and or organizational resilience are still limited to date.